Methodological Approaches to Metaphor Identification in Political Media Discourse: A Corpus-Based Perspective - Soatmurodova, Dinora O‘ktamovna (The Lingua Spectrum, 2026)
Metaphor is an important linguistic tool in political media discourse, as it helps represent political events, social problems and public actors through more concrete domains such as war, journey, disease, natural force or construction (Lakoff & Johnson, 1980; Semino, 2008). However, metaphor analysis requires a systematic method, because selecting only “interesting” examples may make the research subjective. This article discusses several approaches to metaphor identification from a corpus-based perspective: MIP (Pragglejaz Group, 2007), MIPVU (Steen et al., 2019), Critical Metaphor Analysis (Charteris-Black, 2004) and DMIP (Reijnierse et al., 2018). It argues that these methods can be combined: MIP and MIPVU help identify metaphorical language, DMIP helps distinguish deliberate metaphor, while Critical Metaphor Analysis explains rhetorical and ideological functions. Corpus tools support the process by showing frequency, collocations and repeated patterns, but manual contextual analysis remains necessary. Therefore, the article proposes a combined model that includes corpus search, manual identification, annotation, quantitative comparison and qualitative interpretation.